Activities of NGO Initiatives in the field of truth and reconciliation - Kostadinović Bojana (Temida)
Initiatives is regional NGO located in Prokuplje, which have been working on different truth and reconciliation projects. The main target group in their work are young people. The project I have some memories has been conceived to lend support to the young in the process of recovery, forming of genuine values and preparing for reconciliation in the region. Another project is the magazine The Young for the Future, (Published in three languages Serbian, Albanian and English) that is the result of the work of the young from Serbia and Kosovo at the workshops that were held on Kopaonik in December 2003 and February 2004.